Together we re strong - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Writing from Sibiti in southern Congo, Jonas Maboundou, reports that 'thanks to the kindly collected supply of information in Spore, I established a farmers group a cooperative in the making in January 2002. Main activities of the group,...